Judging the cross on rings: a matter of achieving shape constancy - Plessner, Henning; Ahlsdorf, Elke (Applied cognitive psychology, 2005)
The present study examines the influence of viewing position, experience, processing time, and attention on shape constancy in gymnastics judging. In an experiment, 40 gymnastics judges and as many laypeople were presented with a series of photographs that show athletes holding a ‘cross on rings’. They were simultaneously taken from different viewpoints. Participants had to judge how many degrees the arms deviated from horizontal for each picture. One half of the participants had a secondary task, to judge the duration of the picture presentation, which varied also. The overall performances of the gymnastics judges were much better than those of the laypeople, and in contrast to the lay-judgments, they were not influenced by the secondary task. However, gymnastics judges were still significantly influenced by viewpoint, that is, their error rate increased with an increase in deviation from a frontal view. Copyright © 2005 John Wiley & Sons, Ltd.